A DIMENSÃO EMOCIONAL E O TRABALHO DOCENTE: UM ESTUDO A PARTIR DE HUMBERTO MATURANA - Marques, Aline Teotonio (2013)
There are many studies which show the importance of considering emotion/affection in the teaching-learning process as emotion and cognition are inseparable. Accordingly, this paper discusses the relationship between emotion and education through the works of Chilean biologist Humberto Maturana, analyzing how education students (majors and pedagogy) relate to the thrill teaching. For Maturana, the emotion is not restricted to the affective aspect or even subjective or psychic states, nor is it a feeling. It is, above all, in the ways of action, an observing subject construction from a fundamental constitutive emotion, thus structuring, and that drives all other human actions. The author brings the emotion and education as a shift in paradigm which regarded the body and mind as fragments and begins to understand the human as a whole, as a complex that is realized in language and rational, beginning from the emotional. This research sets longitudinal side view research of the program "Social Representations of majors and pedagogy on the teaching work", which is done by the International Center for Research on Social Representations and Subjectivity - Education (CIERS-ed), between 2006 and 2011, under the coordination of Professor. Dr. Clarilza Prado de Sousa. Starting from the assumption that the discursive production of survey reveals how in the world they are located and how they understand their own formation, the present study had analyzed the Database in systematic Research Program to examine, even in indirectly way, how students understand the emotion in teaching. For this purpose, we used data of free association, classification and multiple interviews that, although they have not been concerned directly address the issue of affection and emotion, they allowed an analysis on that direction. The results indicates to a teacher training that see the emotion in teaching, but the training still feel sistress when thinking about the relationship of education.